Treatment of testosterone deficiency syndrome in obese men with type 2 diabetes - Y.V. Luchytskyi; H.A. Zubkova; V.M. Rybalchenko; V.Y. Luchytskyi; I.I. Skladanna (Publishing House TRILIST, 2022)
Objective: to study the effect of testosterone replacement therapy and aromatase inhibitors on the state of androgen supply in men with type 2 diabetes mellitus (DM-2) with obesity. Materials and methods. We examined 38 men aged 37 to 62 years with DM-2 and obesity (main group) and 82 practically healthy men (control group). Blood concentration of luteinizing hormone (LH), total testosterone (Ttot), estradiol (E2) was determined by enzyme immunoassay. T concentration below 8.0 nmol/l was regarded as a sign of hypogonadism, the criterion for hyperestrogenemia was an increase of E2 level over 46 pg/ml. The criterion for obesity was a body mass index > 30 kg/m2. Results. The average serum level of Ttot was significantly reduced compared to the control group. The average levels of E2 in patients of the main group did not differ from the control group. Determination of the average LH levels in the main group showed no probable difference compared to the same indicators in the control group. The Ttot/E2 ratio was lower in men with DM-2 and obesity, but this difference did not reach statistical significance. The Ttot/LH coefficient, which characterizes the effect of endogenous LH on the androgen-producing function of the testicles, was significantly decreased in the main group compared to the control group. Testosterone replacement therapy significantly increased (p < 0.05) the mean blood levels of T. The average E2 levels increased in the dynamics of this therapy, but did not go beyond the normal range for adult men. Letrozole 1.25 mg 1 time per day every other day for 3 months had a positive effect. The E2 levels decreased from 30 to 60%, which was accompanied by an increase of the T concentration by 1.5-6.5 times compared with the baseline levels. Conclusions. DM-2 and obesity are factors in the development of testosterone deficiency syndrome in men. A promising area for research is the use of aromatase inhibitors in men with DM-2, obesity, and testosterone deficiency syndrome caused by hyperestrogenemia.